2011
DOI: 10.1088/0004-6256/142/1/15
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Proper Motion Program. Iv. The Spm4 Catalog

Abstract: We present the fourth installment of the Yale/San Juan Southern Proper Motion Catalog, SPM4. The SPM4 contains absolute proper motions, celestial coordinates, and B, V photometry for over 103 million stars and galaxies between the south celestial pole and -20 • declination. The catalog is roughly complete to V =17.5 and is based on photographic and CCD observations taken with the Yale Southern Observatory's double-astrograph at Cesco Observatory in El Leoncito, Argentina. The proper-motion precision, for well-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 39 publications
3
123
0
Order By: Relevance
“…The Tycho-Gaia Astrometric Solution (TGAS, Lindegren et al 2016) from the Gaia data release 1 provides trigonometric parallaxes and proper motions for 203 stars in our sample. To access more proper motion data, we also searched for this information in the PPMXL (Roeser et al 2010), UCAC4 (Zacharias et al 2012) and SPM4 (Girard et al 2011) catalogs. Doing so, we find proper motions for 368 stars of the sample.…”
Section: Appendix A: Ad Hoc Force To Account For Type II Migrationmentioning
confidence: 99%
“…The Tycho-Gaia Astrometric Solution (TGAS, Lindegren et al 2016) from the Gaia data release 1 provides trigonometric parallaxes and proper motions for 203 stars in our sample. To access more proper motion data, we also searched for this information in the PPMXL (Roeser et al 2010), UCAC4 (Zacharias et al 2012) and SPM4 (Girard et al 2011) catalogs. Doing so, we find proper motions for 368 stars of the sample.…”
Section: Appendix A: Ad Hoc Force To Account For Type II Migrationmentioning
confidence: 99%
“…In order to further investigate the nature of our sample stars, we extracted their proper motions from two sources: the Southern Proper Motion Catalog 4 (SPM4; Girard et al 2011) and The Fourth US Naval Observatory CCD Astrograph Catalog (UCAC4; Zacharias et al 2013). As Fig.…”
Section: Kinematicsmentioning
confidence: 99%
“…We do not use proper motions, or stellar parameters that could in principle provide tighter constraints, but then one has to worry about the systematics introduced by their use. For example, in a recent kinematic analysis of RAVE stars, Williams et al (2013) found systematic differences between different proper-motion catalogs like PPMXL (Röser et al 2008), SPM4 (Girard et al 2011), and UCAC3 (Zacharias et al 2010). As for stellar parameters, although they are reliable, no pipeline can claim to be free of unknown systematics, especially when working with low signalto-noise ratio data.…”
Section: Rave Surveymentioning
confidence: 99%